Ta'ṡīru Ḥifẓi al-Qur'ān fī al-Istī‘āb 'Ala al-Mufradāt al-‘Arabiyyah Ladā at-Ṭullab bi Ma'hadi Ar-Rahmah li Taḥfīẓi al-Qur'ān bi Balikpapan - Tatang Hidayat; Sadiyah Ratnasari Sagala; Istianah Istianah; Husnul Khatimah; Muhammad Nanang Qosim; Abdel Rahman Elsayed Elsayed Abdel Ghaffar Balah (University of Darussalam Gontor, 2024)
This research aims to find out the influence of the ability to memorize the Qur'an on the Arabic vocabulary mastery among students of the boarding school for tahfīdz Qur’an Balikpapan, and follows the analytical descriptive approach to this goal. The methods used by the researcher to collect data are testing, observation and documentation. It is quantitative research with the design of causal association research with a sample of 31 students from the second stage in the preservation of the Qur'an. For data analysis, the researcher used regression equation, selection factors and importance testing. The results of this research show that there is a significant impact of the preservation of the Qur'an with the mastery of Arabic vocabulary. By calculating the importance test analysis that indicates that tvalue (7,482) is greater than ttable (2,045), H0 was rejected and H1 was accepted, which means that there is a significant influence between the ability to memorize the Qur’an to the Arabic vocabulary mastery. The percentage of the influence of Qur'anic memorization ability on the ruling of Arabic vocabulary is 65.9%, and 34.1% by other factors. Keywords: Memorization, Al-Qur'an, Mastery, Arabic Vocabulary, Boarding School for Tahfīdz Qur’an